2016
DOI: 10.1007/s00406-016-0702-9
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HTTLPR and BDNF polymorphisms moderate the association between uncinate fasciculus connectivity and antidepressants treatment response in major depression

Abstract: Symptom improvement in depression due to antidepressant treatment is highly variable and clinically unpredictable. Linking neuronal connectivity and genetic risk factors in predicting antidepressant response has clinical implications. Our investigation assessed whether indices of white matter integrity, serotonin transporter-linked polymorphism (5-HTTLPR) and brain-derived neurotrophic factor (BDNF) val66met polymorphism predicted magnitude of depression symptom change following antidepressant treatment. Fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 68 publications
5
20
0
Order By: Relevance
“…It is also conceivable that the association between structural coupling and genetic variations is more pronounced in interaction with stressful conditions, like the development of psychiatric disorders or stressful life events. In line with this notion, a series of studies found no main effects but (only) interaction effects between FA-values and 5-HTTLPR on specific psychiatric symptoms and treatment responses for different tracts and psychiatric disorders (Tatham et al, 2016 , 2017 ). In congruence with this, Kelly et al ( 2014 ) also observed similar findings for further genotypes by showing no association between specific different genetic variations (e.g., for schizophrenia) and white matter alterations in healthy subjects, which already has been confirmed in meta-analyses for patients (Ellison-Wright and Bullmore, 2009 ).…”
Section: Discussionmentioning
confidence: 91%
“…It is also conceivable that the association between structural coupling and genetic variations is more pronounced in interaction with stressful conditions, like the development of psychiatric disorders or stressful life events. In line with this notion, a series of studies found no main effects but (only) interaction effects between FA-values and 5-HTTLPR on specific psychiatric symptoms and treatment responses for different tracts and psychiatric disorders (Tatham et al, 2016 , 2017 ). In congruence with this, Kelly et al ( 2014 ) also observed similar findings for further genotypes by showing no association between specific different genetic variations (e.g., for schizophrenia) and white matter alterations in healthy subjects, which already has been confirmed in meta-analyses for patients (Ellison-Wright and Bullmore, 2009 ).…”
Section: Discussionmentioning
confidence: 91%
“…For instance, reduced apathy in response to treatment with selective serotonin reuptake inhibitors (SSRIs) was found to significantly correlate with greater FA in the UF (Yuen et al, ), and FA abnormalities in the left UF were found to resolve after SSRI treatment (Zheng et al, ). Interestingly, MDD carriers of the brain‐derived neurotrophic factor (BDNF) Met allele were recently found to have lower FA in the UF than subjects homozygous for the Val allele; the same study reported correlations between FA and severity of depression that were modulated by both BDNF genotype and the 5‐HTTLPR genotype (Tatham, Hall, Clark, Foster, & Ramasubbu, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no significant interaction between the BDNF Val66Met polymorphism and DTI findings [99]. An imaging genetic study that investigated DTI-TBSS and polymorphisms (BDNF Val66Met and 5-HTTLPR) found that the predictive value of white matter connectivity in antidepressant response may be influenced by genetic polymorphisms in MDD [100]. In this previous study, the interaction between 5-HTTLPR polymorphisms and FA value in the right uncinate fasciculus predicted the change in MDD severity [100].…”
Section: Imaging Pharmacogeneticsmentioning
confidence: 69%
“…An imaging genetic study that investigated DTI-TBSS and polymorphisms (BDNF Val66Met and 5-HTTLPR) found that the predictive value of white matter connectivity in antidepressant response may be influenced by genetic polymorphisms in MDD [100]. In this previous study, the interaction between 5-HTTLPR polymorphisms and FA value in the right uncinate fasciculus predicted the change in MDD severity [100]. Recently, the machine learning model called the ensemble learning prediction model showed improvements in sensitivity and accuracy of prediction after integrating imaging and genetic data [101].…”
Section: Imaging Pharmacogeneticsmentioning
confidence: 99%